Spotlight on Cloud : Public Interest Technology with Bruce Schneier - Schneier, Bruce (O'Reilly Media, Inc., 2020)
Information security, IoT safety, data privacy, algorithmic security and fairness, AI, biotech, the future of work-information technology is now a public policy issue. But while an understanding of the technology involved is fundamental to crafting good policy, there's little involvement of technologists in policy discussions. This isn't sustainable. We need public interest technologists: people from our fields helping craft policy and providing security to agencies and groups working in the broader public interest. We need them in government, at NGOs, teaching at universities, as part of the press, and inside private companies. This is increasingly critical to both public safety and overall social welfare In this Spotlight on Cloud , find out about the current state of public interest technology and to discover a way forward, for us individually and collectively for our field. Recorded on December 5, 2019. See the original event page for resources for further learning or watch recordings of other past events . O'Reilly Spotlight explores emerging business and technology topics and ideas through a series of one-hour interactive events. In live conversations, participants share their questions and ideas while hearing the experts' unique perspectives, insights, fears, and predictions for the future. In every edition of Spotlight on Cloud , you'll learn about the complex, ever-evolving world of the cloud. You'll discover how successful companies have adopted and embraced this massive network of shared information and how you can follow their lead to transform your organization and prepare for the Next Economy.